Strategi UMKM Mempertahankan Pelanggan: Keberagaman Produk, Transparansi, dan Kemudahan Integrasi Media Sosial - Darmawan, Didit; Mulyanto, Feri Dwi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This literature study aims to analyze the strategies of product differentiation through MSME product variety, trust building through producer transparency, and ease of social media integration in influencing online store customer retention. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that product variety relevant to market needs creates attractiveness and encourages consumer exploration. Varied products provide more choices and increase opportunities for consumers to find suitable items. Producer transparency regarding raw materials, production processes, sales policies, and honest communication builds a solid foundation of trust. Trusting consumers feel safe and comfortable transacting. Ease of social media integration creates seamless shopping experiences, personal interaction, and responsive service that strengthen relationships with consumers. These three strategies complement each other and collectively create an ecosystem that encourages consumers to remain loyal and make repeat purchases. This study contributes theoretically to enriching digital marketing and entrepreneurship literature with a customer retention perspective on MSMEs and practically provides foundations for MSME actors in designing product development strategies, transparency values, and social media optimization to increase competitiveness in the digital market.